Impact-induced compaction of primitive solar system solids: The need for mesoscale modelling and experiments - Davison,TM; Derrick,JG; Collins,GS; Bland,PA; Rutherford,ME; Chapman,DJ; Eakins,DE (Procedia Engineering, 2017)
Primitive solar system solids were accreted as highly porous bimodal mixtures of mm-sized chondrules and sub-μm matrix grains. To understand the compaction and lithification of these materials by shock, it is necessary to investigate the process at the mesoscale; i.e., the scale of individual chondrules. Here we document simulations of hypervelocity compaction of primitive materials using the iSALE shock physics model. We compare the numerical methods employed here with shock compaction experiments involving bimodal mixtures of glass beads and silica powder and find good agreement in bulk material response between the experiments and models. The heterogeneous response to shock of bimodal porous mixtures with a composition more appropriate for primitive solids was subsequently investigated: strong temperature dichotomies between the chondrules and matrix were observed (non-porous chondrules remained largely cold, while the porous matrix saw temperature increases of 100’s K). Matrix compaction was heterogeneous, and post-shock porosity was found to be lower on the lee-side of chondrules. The strain in the matrix was shown to be higher near the chondrule rims, in agreement with observations from meteorites. Chondrule flattening in the direction of the shock increases with increasing impact velocity, with flattened chondrules oriented with their semi-minor axis parallel to the shock direction.